Diversity of microbes in organic and non-organic vegetable ecosystem. Issue 1 (April 2020) - Sylvia, S; Rahim, H; Surapati, U; Rosmana, A; Dewi, V S
Abstract: This study aims to determine microorganisms in organically managed land. The study was conducted in the organic land and non-organic farmer's land in Makassar and continued at the Disease Sciences laboratory, Department of Pests and Plant Diseases, Faculty of Agriculture, Universitas Hasanuddin. The stages of the study consisted of soil sampling and 10 grams were taken to be diluted into 90 ml of sterile water, then a 10-3 dilution was carried out. The results of the dilution are taken 1ml each and then poured into the PDA media. The fungus that grows is purified on PDA media while bacteria on NA media, then identified. The results showed that in organic vegetable fields more fungi isolates were found (6 isolates): Gliocladium sp, Rhizoctonia sp, Aspergillus sp and two other isolates were unknown and gram-positive bacteria were found while non-organic was found five fungus isolates, Scopulariopsis sp., Verticillium sp., Fusarium sp., Gliocladium sp, Percentage of inhibition of fungi from organic vegetable fields ranged from 33.3 to 100% while non-organic lands 16.7 to 66.7%.